Wild animals and constitutional procedural law - Monsalve Mantilla, Milton Dubán (DIXI, 2021)
Introduction: In Colombia, constitutional procedural law and the actions contemplated in the Political Constitution, especially habeas corpus, the popular action and the tutela action, have a marked anthropocentric destination, which makes their use in favor of other animal species inoperative. Methodology: Through a descriptive documentary analysis, the nature of constitutional procedural law and its incidence on the protection of wild animals in Colombia is investigated, reviewing jurisprudence and analyzing sources. Findings: Although progress has been made in laws that impact animal protection, the protection and conservation of animal species, via jurisdictional means, will be nugatory as long as new actions are not created exclusively in favor of non-human animals (recognizing a new specialty such as animal law), or as long as the general interest of the animal is rewarded over the formalism of constitutional procedural law. Conclusions: The Constitutional Court, in Unification Ruling 016 of January 2020, determined that habeas corpus is only appropriate for the protection of the fundamental right to freedom of persons, and it is not possible to use it in the case of non-human animals. The protection and conservation of animals constitutes a collective right in accordance with articles 8, 79, 80, 88, 95-8 of the Political Constitution for which a popular action is appropriate. However, the dependence of “animal law” on other specialties of law, in the precise case of “constitutional procedural” law, has caused obstacles in the real and effective protection of wild animal species in Colombia.